Analysis and Development of Cocoa Agribusiness in Kare Village, Madiun District, East Java - Nisa Hafiidhoh Fitriana; Indra Tjahaja Amir; Pawana Nur Indah (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2020)
Cocoa is one of the plantation commodities whose role is quite important for the national economy, especially as a provider of employment, a source of income, and foreign exchange. Financial profit is a necessity in exploiting a commodity. The market aspect is one of the determining factors for the success of cocoa plantation operations. So the results of the analysis above are combined with stakeholder opinions on the development of cocoa agribusiness. The objectives of this study are: 1) Analyzing the financial feasibility of cocoa farming 2) Analyzing cocoa farming chain and marketing margins 3) Identifying stakeholders' opinions on alternative decision making for cocoa agribusiness development 4) Developing cocoa agribusiness development directives. Financial feasibility analysis methods (NPV, Net B / C, IRR, Payback Period, and Sensitivity Analysis), marketing analysis (chain analysis and marketing margins), and Analytical Hierarchy Process (AHP). The results showed that: (1) Cocoa farming is feasible to be developed financially, because the value of NPV> 0, Gross B / C> 1, Net B / C> 1, IRR> applicable interest rate, and return on capital with a time limit less than 20 years. The sensitivity of cocoa farming occurs in decreasing production. Where cocoa farming is still feasible if these conditions occur. (2) Marketing chains and margins, namely, there are two cocoa marketing channels, marketing margins of IDR 5,000 and IDR 2,000. (3) The selection of alternatives that greatly affect the development of cocoa agribusiness is market factors, HR factors, and technology factors. The direction of agribusiness development needed is the availability of a market that has stable cocoa prices for farmers, the availability of skilled human resources in cultivation and post-harvest technology that is able to provide greater added value to cocoa.